ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARI'AH DENGAN PERBANKAN KONVENSIONAL - Diah Tri Susanti; Akhmad Sakhowi; Mahirun Mahirun (Jurnal Ekonomi Dan Bisnis, 2019)
This  study  aims to analyze  the  financial  performance  comparison  between  Islamic  banking  and  conventional banking,  using  profitability  ratios  are  represented  by Return  on Assets (ROA) as  dependent  variables  and analyze  the  variables  that affect the  profitability  of banks is Finance  to  Deposit  Ratio  (FDR),  Ratio  Operating costs  with  Revenues  Operations  (BOPO), Adiquasi Capital  Ratio  (CAR) and  Reserve  Elimination  Receivables (PPAP).Methods  using multiple linear regression analysis, chow test and independent sample t-test (test dlff], sample uses three  Islamic  banks and  conventional,  while the  data  used  are  secondary  data  are  reported  quarterly financial reports to Bank Indonesia as well as publicized the period June 2007 - June 2010.The results  showed that  in  Islamic banking,  CAR and PPAP no significant  positive effect on ROA, LOR and no significant negative effect on ROA. BOPO significant negative effect on ROA. In conventional banking, LOR is not significant  positive  effect  on  ROA,  CAR and  PPAP  no significant  negative  effect  on  ROA.  BOPO significant negative effect on ROA. Chow test results states that there are significant differences in the influence of four independent variables on ROA in Islamic banking and conventional  banking.Different test states that the  ROA ratio, LOR and PPAP  Islamic banking is better than conventional  banking, and there are significant differences, for  BOPO ratio  is better than the  conventional  banking and Islamic banking there Is no significant difference,Keyword : Islamic Banking, Conventional Banking, ROA, LDR, BOPO, CAR, PPAP